Thrombectomy from superior mesenteric vein in treatment of small intestine gangrene - Ihnatovich I; Ihnatovich K (Archives of Clinical Gastroenterology - Peertechz Publications, 2020)
The traditional definition of tissue ischemia-a decreased level of oxygen deliverability by bloodstream that results in cell hypoxia. Anatomical and functional hindrance to blood flow is the basis of tissue hypoperfusion. Arterial, venous and functional disturbances in blood circulation lead to acute intestinal ischemia. In 85-90 % of cases acute mesenterial ischemia was caused by arterial reasons: thrombosis or embolism. Venous thrombosis is responsible for 10%-15% of acute mesenterial ischemia cases.